2019
DOI: 10.3390/nu11061268
|View full text |Cite
|
Sign up to set email alerts
|

Serum n-6 Fatty Acids are Positively Associated with Growth in 6-to-10-Year Old Ugandan Children Regardless of HIV Status—A Cross-Sectional Study

Abstract: Fatty acids (FAs) are crucial in child growth and development. In Uganda, antiretroviral therapy (ART) has drastically reduced perinatal human immunodeficiency virus (HIV) infection of infants, however, the interplay of FAs, ART, and HIV in relation to child growth is not well understood. To investigate this, serum was collected from 240 children between 6–10 years old in Uganda and analyzed for FAs using gas-chromatography mass-spectrometry. HIV status and anthropometric measurements were taken, and relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 40 publications
3
17
1
Order By: Relevance
“…Three hundred and five Ugandan children (6-10 years old) with and without HIV infection were enrolled from the Kawaala Health Center (KHC) in Kawempe Division of Kampala, Uganda, as part of a 12-month prospective cohort study (20) . Of these, serum levels of PUFA were available for 237 children including perinatally acquired HIV infection (CPHIV, n 82), perinatally HIV exposed but uninfected (CHEU, n 76) and HIV unexposed uninfected (CHUU, n 78) community control children that constituted the study sample for this investigation.…”
Section: Study Samplementioning
confidence: 99%
See 3 more Smart Citations
“…Three hundred and five Ugandan children (6-10 years old) with and without HIV infection were enrolled from the Kawaala Health Center (KHC) in Kawempe Division of Kampala, Uganda, as part of a 12-month prospective cohort study (20) . Of these, serum levels of PUFA were available for 237 children including perinatally acquired HIV infection (CPHIV, n 82), perinatally HIV exposed but uninfected (CHEU, n 76) and HIV unexposed uninfected (CHUU, n 78) community control children that constituted the study sample for this investigation.…”
Section: Study Samplementioning
confidence: 99%
“…Of the total samples shipped, 237 were analysable for FA. FA were extracted and methylated from serum as previously described (20) . A modified methylation described by Jenkins (2010) was conducted (22) .…”
Section: Serum Fatty Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…This unstable association of sdNVP ± ZDV with adaptive skills over 12 months beginning from age 6–10 years, if true, may suggest that sustaining the cognitive advantage of a beneficial exposure in the long term requires intentional efforts to optimize current biopsychosocial circumstances. Our team has recently reported on the importance of high‐quality nutrition [47,48] and stress [49,50] in relationship to cognition in this sample. With respect to stress, we found that SEA, QOL and psychosocial adjustment of CPHIV are comparable to CHEU and HUU peers in Uganda among children of caregivers who reported low psychosocial stress.…”
Section: Resultsmentioning
confidence: 99%